On Being (Not) Old: Agency, Self‐care, and Life‐course Aspirations in the United States. (4th April 2019) - Lamb, Sarah
Abstract: This article examines U.S. endeavors to eradicate old age. Drawing on research with older, mostly white, Americans across social classes, I probe how older people engage in "healthy, " "successful" aging as a moral project, health identity, and way of approaching the life course. Moving beyond influential literature on biopolitics and biomedicine that tends to treat medicine, science, and biopolitical governance as overdetermined causal forces, I explore instead how a confluence of factors—including cultural ideologies of personhood and independence, medical interventions, social hierarchies, and individual experiences—together lead to the stigmatization of oldness. Social inequalities also matter, as an ethos of self‐care and individual agency to ward off oldness is most pronounced among the able‐bodied and socioeconomic elite. The aim is to illuminate the convergence of factors that stigmatize oldness in contemporary North America, while highlighting the ways that class profoundly figures in people's varied attempts to not be old.